1986
DOI: 10.1557/jmr.1986.0564
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-recoil damage in zirconolite (CaZrTi2O7)

Abstract: Radiation effects in a natural, metamict zirconolite from Sri Lanka that has received an alpha-decay dose greater than lo2' alpha decays/m' have been studied using x-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), electron paramagnetic resonance spectroscopy ( EPR), extended x-ray absorption fine structure spectroscopy (EXAFS), and x-ray absorption near edge structure spectroscopy (XANES). The same techniques were applied to the sample annealed between 1000" and 1100 "C. The he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…Synthetic and to a smaller extent natural pyrochlores with a broad range of different cation substitutes have been thoroughly investigated [16,[34][35][36][37][38][39][40][41]. Gregg et al [42] observed additional Raman modes between 700 and 800 cm −1 related to U-impurities in the pyrochlore structure.…”
Section: Hementioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic and to a smaller extent natural pyrochlores with a broad range of different cation substitutes have been thoroughly investigated [16,[34][35][36][37][38][39][40][41]. Gregg et al [42] observed additional Raman modes between 700 and 800 cm −1 related to U-impurities in the pyrochlore structure.…”
Section: Hementioning
confidence: 99%
“…Gregg et al [42] observed additional Raman modes between 700 and 800 cm −1 related to U-impurities in the pyrochlore structure. The annealing-induced recrystallization behavior of moderately to fully metamict, altered natural pyrochlores has been followed among others by differential thermal and thermogravimetric analysis (DTA/TG), revealing strong exothermic reactions and a noticeable weight loss [37,38,43].…”
Section: Hementioning
confidence: 99%
“…The decrease in the L-L* energy difference is associated with a change in the titanium coordination number from an octahedral (pristine region) to a tetrahedral (amorphous region) coordination [4] [24]. The correlation between the decrease of cation coordination number and amorphisation has been reported previously in studies performed by Extended X-ray Absorption Fine structure (EXAFS) and X-ray Absorption Near Edge Structure (XANES) on similar materials [39][40] [41]. No significant change in the L-L* energy difference is observed in the partly damaged regions.…”
Section: Kr Irradiated Samplesmentioning
confidence: 75%
“…The defects along the twin boundaries may become sites at which actinide elements are incorporated. In some instances [44], there was evidence for the formation of crystals (5-100 nm) with d -spacings similar to those of the fluorite structure type. Lumpkin et al [a] suggested that metamict zirconolite may recrystallize initially with a disordered, fluorite-type structure.…”
Section: Waste Forms For Piutoniummentioning
confidence: 98%